The Juridical Formulation of Hate Speech Cyber Crime and Its Law Enforcement Implementation - Ismanto, Hadi; Gunarto, Gunarto; Endah Wahyuningsih, Sri (Law Development Journal, 2021)
The purpose of this paper is to analyze the juridical formulation of Article 28 paragraph (2) and Article 45 paragraph (2) of the ITE Law and the implementation of law enforcement. The method used is normative juridical. The research results obtained that the juridical formulation of Article 28 paragraph (2) in conjunction with Article 45 paragraph (2) of the ITE Law, contains several juridical weaknesses that it does not formulate the qualifications of the offense whether it is "violation" or "crime" law enforcement. The origin of 28 paragraph (2) is proven through a meaningful analysis of the content of the accused's hate speech phrases that actually cause hostility, communal conflicts through the symbolization of religious figures.